Mentoring Program on Traditional Culinary Menu for Gastrodiplomacy in Bilebante Green Tourism Village: Pendampingan Pengembangan Menu Kuliner Tradisional untuk Gastrodiplomasi di Desa Wisata Hijau Bilebante - Nurhayati, Hastuti; Mandra, Mandra (RADIANT: Journal of Applied, Social, and Education Studies, 2025)
This independent community service program aims to help address the challenges faced by the partner, particularly their limited knowledge and skills in preparing international-standard menus for the Gastrodiplomacy Local Experience event, which was attended by 38 countries and held in the Green Tourism Village of Bilebante. The program began with a pre-field stage involving observation, semi-structured interviews, participatory observation, and focus group discussions over three days to identify the partner’s needs and challenges. During the implementation stage, menu planning was carried out collaboratively with seven tourism village managers, including the head of the Tourism Awareness Group (POKDARWIS), culinary business operators, and the person in charge of the culinary division from the local working group (POKJA). The mentoring produced two internationally standardized menu sets consisting of appetizers, soups, main courses, and desserts. The dishes were presented traditionally using the communal begibung concept while being adjusted to international tastes by emphasizing local uniqueness and wisdom. Feedback from the 38 diplomatic delegates on the presented menus was largely positive. The collaboration of local ingredients, traditional values, and global sustainability principles highlighted the role of cuisine as a communicative and transformative diplomatic medium. These outcomes demonstrate the contribution of local cuisine in shaping Indonesia’s image and strengthening the position of local communities in international-standard hospitality. In the future, similar activities are expected to continue, aiming to enhance the capacity of rural communities to adapt to the dynamics of global tourism without neglecting their cultural roots.